2005
DOI: 10.1029/2004gl021445
|View full text |Cite
|
Sign up to set email alerts
|

Intermittency analyses on the SIERRA measurements of the electric field fluctuations in the auroral zone

Abstract: [1] We perform intermittency analyses on the electric field data obtained by the SIERRA sounding rocket in the auroral zone. The electric field fluctuations are broadband, covering the extremely low-frequency range with a power-law relation, similar to the type of fluctuations commonly observed at various altitudes of the auroral region. Our preliminary analyses of the data based on the technique of probability distribution functions indicate that the electric field fluctuations are intermittent in the spacecr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
52
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 18 publications
10
52
1
Order By: Relevance
“…To examine these fields, we applied the technique of the generalized structure function and probability density function, and demonstrated that they generally have scaling properties similar to those of the turbulent electric fields in the auroral zone [Tam et al, 2005]. The observed scaling features are in a good agreement with the scenario proposed by Chang et al [2004].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…To examine these fields, we applied the technique of the generalized structure function and probability density function, and demonstrated that they generally have scaling properties similar to those of the turbulent electric fields in the auroral zone [Tam et al, 2005]. The observed scaling features are in a good agreement with the scenario proposed by Chang et al [2004].…”
Section: Discussionsupporting
confidence: 56%
“…A similarity between the turbulence and discrete auroral features with respect to the global distribution, seasonal variation, relation to solar wind, IMF and geomagnetic conditions has been pointed out by Heppner [1973], Saflekos and Potemra [1978], Golovchanskaya et al [2002], and Matsuo et al [2003]. Recently, Tam et al [2005] have performed intermittency analysis on the electric field data obtained by a sounding rocket in the auroral zone. By examining the PDF and local intermittency measure, they evidenced the intermittent turbulence for the broadband ELF electric field fluctuations and showed that the degree of intermittency is larger at smaller scales.…”
Section: Introductionmentioning
confidence: 97%
“…As evident from the analysis, our diagnostic is based on structure functions of the electrostatic potential. Other related works (Tam et al, 2005) are based on wavelet transforms. They studied the degree of intermittency on different scales and found electric field fluctuations to be more intermittent on smaller scales.…”
Section: Discussionmentioning
confidence: 99%
“…Such waves are often spontaneously excited in nature by plasma instabilities and have been frequently observed also in the Earth's ionosphere. Intermittency effects have been studied in the ionospheric plasma by, for instance, Tam et al (2005), where their work refers to ∼700 km altitudes. Other relevant studies of space plasma turbulence can be found in the work by Chang and Wu (2008).…”
Section: Introductionmentioning
confidence: 99%
“…Such has been the case, for instance, for the measured fields in the solar wind, magnetospheric cusp, plasma sheet and the auroral zone (Burlaga, 1991;Bruno et al, 2001;Weygand et al, 2005;Tam et al, 2005;Echim et al, 2007). The origin of intermittent fluctuations in magnetized plasmas was interpreted as the result Correspondence to: S. W. Y.…”
Section: Introductionmentioning
confidence: 94%